The Knowledge, Experiences, and Barriers Associated with Male Involvement in Family Planning at Tehsil Lal Qila, District Dir (Lower), KPK, Pakistan: Experiences and Barriers Associated with Male Involvement in Family Planning - Khan, Jalal; Ali, Tazeen Saeed; Shah, Nasim Zahid; Khan, Inayatullah (Pakistan Journal of Health Sciences, 2025)
Pakistan is one of the world’s most populous countries, with a high growth rate affecting the country’s socioeconomic progress negatively. Family Planning (FP) can reduce fertility rates, enhance maternal and child health. With the use of FP, mothers will have a low risk of pregnancy-related complications, and the best care can be provided to a child. Moreover, FP has a significant role in accelerating the Sustainable Development Goals (SDGs). Investing in FP will lower poverty and improve economic stability. Objectives: To explore the knowledge, experiences, and barriers associated with male involvement in family planning in Tehsil Lal Qila, Dir Lower, KPK. Also, to propose strategies to promote male participation in FP through improved awareness, accessibility, and inclusion in reproductive health programs. Methods: A qualitative exploratory design was used with a total of 12 in-depth interviews with male clients using a purposive sampling technique. The data were analysed using content analysis. Results: Myths and misbeliefs about FP, the unavailability and unaffordability of contraceptives, pressure from intimate partners and relatives, lack of proper FP services, and gender discrimination were significant barriers to the use of FP. Conclusions: Collaborative efforts among various stakeholders, for instance, community-level awareness campaigns, accessible and affordable FP services, male involvement in healthcare initiatives (alongside females), and improved communication skills among healthcare providers working in FP programs can promote the use of FP.